Biologia reprodutiva de Copaifera langsdorffii Desf. (Leguminosae, Caesalpinioideae) - Freitas, Cristiane V. (2002)
A survey on the phenology and reproductive biology of Copaifera langsdorffii Desf. was carried out in a cerradão area at Fazenda Capim Branco, Uberlândia, MG. Flowering occurs during the rain season and seed dispersal during the dry season. Flowers are pale-green, 0.5 cm in diameter, weakly zigomorphic and organized in paniculate inflorescences. They are highly odoriferous, one-day flowers. Anthesis begins at about 5:00 h. The nectar production is very small (0.2 ml) with 49% of sucrose equivalents. The most frequent flower visitors and pollinators were Apis mellifera, Scaptotrigona cf. depiles and Trigona spinipes bees. Controlled hand-pollinations showed that the species is mostly self-sterile and non-apomictic. However, pollen tubes were observed growing down to the ovary and penetrating the ovules in self-pollinated pistils, a fact which suggests late-acting self-sterility phenomena or inbreeding depression. Fruit-set was always low and related to low flower to fruit conversion, may be due to inefficient pollination and fruit predation.